2020
DOI: 10.31557/apjcp.2020.21.5.1303
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure and Risk Assessment of Formaldehyde in the Pathology Departments of Hospitals

Abstract: Background and Objective: Exposure to formaldehyde has adverse effects on health both acutely and over the long term (e.g., carcinogenicity). The substance is widely used in pathology and histology departments. This study focused on cancer risk of formaldehyde in pathology department of five hospitals in Rasht. Materials and Methods: Sampling and determination of formaldehyde in pathology department were carried out based on the NIOSH method of 3500. The working condition and working environment were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 31 publications
1
16
1
1
Order By: Relevance
“…The average and maximum levels observed in this study for formaldehyde exposure are, however, significantly lower than those in other work sectors, such as foundry workers [18], plastic laminate plant workers [19], employees of a wood industry [20], and pathology departments of hospitals [21].…”
Section: Discussioncontrasting
confidence: 67%
“…The average and maximum levels observed in this study for formaldehyde exposure are, however, significantly lower than those in other work sectors, such as foundry workers [18], plastic laminate plant workers [19], employees of a wood industry [20], and pathology departments of hospitals [21].…”
Section: Discussioncontrasting
confidence: 67%
“…In a few studies, exposure to formaldehyde was monitored in pathology laboratory staff through personal and stationary air sampling [45][46][47], and in one study exposure to formaldehyde was assessed by personal air sampling of plastic product workers to estimate their cancer risk [48].…”
Section: Exposure Monitoring Studies Including Cancer Risk Predictionsmentioning
confidence: 99%
“… 9 , 10 The International Agency for the Research on Cancer (IARC) has identified three main occupational scenarios where workers may be exposed to formaldehyde at air concentrations significantly higher than the indoor and outdoor background levels: (i) the production of formaldehyde and/or its solutions; (ii) the production of products containing formaldehyde or during their use and (iii) the combustion of products generating formaldehyde. 8 Thus, workers in industrial production processes (resins, plastics, semi‐finished wood products, furnishing accessories and textiles), 11 , 12 professionals of gross anatomy and pathology laboratories, veterinarians, embalmers, 9 , 10 , 13 , 14 , 15 breeders, 16 carpenters, industrial launderers, 17 firefighters, beauticians and printing‐rooms workers 18 , 19 , 20 are the categories at higher risk of exposure to formaldehyde.…”
Section: Introductionmentioning
confidence: 99%